2012
DOI: 10.1016/j.rppneu.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Preditores de conversão tardia dos exames micobacteriológicos direto e cultural de expetoração numa população portuguesa com tuberculose pulmonar

Abstract: Delayed sputum smear and culture conversion occurred in about one third of patients. Older age, male gender, and higher bacillary load were independently associated with delayed smear conversion. Bilateral radiological involvement and higher colony count were independently associated with delayed culture conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
7
10
0
Order By: Relevance
“…We found higher initial smear grading which was associated with delayed conversion time ( P = 0.01). This finding was observed in previous studies [ 7 , 14 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found higher initial smear grading which was associated with delayed conversion time ( P = 0.01). This finding was observed in previous studies [ 7 , 14 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Treatment outcomes in patients with TB and DM have been a subject of debate. In a study performed in India smear conversion was similar in diabetic and nondiabetic patients [ 17 ], in contrast to another study conducted in México which identified diabetes as an independent risk of failure to treatment [ 19 ]. Defects in the immune system of patients with active TB and DM have been reported, including reductions in the activation of alveolar macrophages and the capacity to produce interleukin [ 20 , 21 ], in addition to some degree of impaired limited numbers of diabetic patients' gastrointestinal drug absorption even in the absence of clinical gastroparesis [ 22 ].…”
Section: Discussionmentioning
confidence: 97%
“…Twenty-four percent of the patients who received extended treatment had delay of sputum smear and culture conversion longer than 2 months. This outcome well corresponded with results of several epidemiological studies indicating that the proportion of TB patients who remain smear-positive after 2 months of treatment can be greater than 20% (3.3–25.3%) [39–48]. However, our multivariable regression analysis did not confirm significant differences in delay of culture conversion between our two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Caetano Mota et al reported that patients with a high pre-treatment colony count were less likely to convert than patients with a low pre-treatment colony count. [ 5 ] In the present study, although sputum smear grading, which is available at an early time point of treatment, was chosen as an index of bacillary load, the result is similar to that of the previous report. It may be natural that patients with a higher colony count take a longer time to convert sputum cultures.…”
Section: Discussionmentioning
confidence: 55%
“…Sputum culture conversion after the first 2 months of treatment is recognized as a surrogate biomarker of long-term cure. [ 2 , 3 ] It has been reported that the presence of cavitation [ 4 ], the extent of the disease [ 5 , 6 ] on chest X-ray (CXR), high colony count, [ 5 ] diabetes mellitus, [ 6 ] and smoking [ 4 , 7 9 ] are associated with culture non-conversion after the first 2 months of treatment. However, no study has evaluated which factors affect the time to sputum culture conversion throughout the course of treatment in a cohort without any censored cases.…”
Section: Introductionmentioning
confidence: 99%